Psychosocial Influences on Fruit and Vegetable Intake Following a NYC Supermarket Discount. Issue 8 (7th June 2017) - Bernales‐Korins, Maria; Ang, Ian Yi Han; Khan, Shamima; Geliebter, Allan
Abstract : Objective: To assess the effect of a 50% discount on fruits and vegetables (F&V) on the purchase and intake of F&V and on psychosocial determinants of F&V intake: self‐efficacy (SE), stages of change (SOC), and perceived barriers (PB). Methods: This randomized controlled trial was conducted in local supermarkets over 16 weeks, including a 4‐week baseline, 8‐week discount intervention, and 4‐week follow‐up. Shoppers with overweight or obesity (BMI > 25) were randomized to receive a discount or no discount via their reward scan card after the baseline. Twenty‐four‐hour recalls and psychosocial measures were obtained for each study period. Results: Purchases ( P  < 0.0005) and intakes ( P =  0.019) of F&V increased significantly during the intervention, while only F&V intake was sustained at follow‐up. The discount intervention increased SE ( P  < 0.01) and SOC ( P  < 0.05) and did not decrease PB ( P  = 0.057) during the intervention. SOC mediated the discount intervention effect on F&V intake ( P  < 0.05) during the intervention, explaining 43% of variance. Conclusions: A supermarket discount intervention led to increases in purchases and intakes of F&V and increases in the psychosocial factors SE and SOC and did not decrease PB. The discount intervention prompted participants to move from the preparation to action stage of SOC, which acted as a mediator for increased F&V intake.